KEBERADAAN JIWA MANUSIA SETELAH KEMATIAN - Odja, Viktorinus Raja (STIPAS TAHASAK DANUM PAMBELUM KEUSKUPAN PALANGKARAYA, 2016)
Human life in this world is not immortal. All men will die. The heavenlywelfare became the life purpose of the Christians. Death became the entranceto the eternal life in the kingdom of heaven. The view of death and faith inlife after death gave hope that all believers have a place in the kingdom ofheaven. After death, the souls of all the faithful will be directly judged at theend of time, all mankind will be judged in front of God. At this point, the soulof the believer will be determined whether to go to the heaven or the hell. Sinand error make the human being must purify them first in purgatory. Theeternal life and heavenly bliss with God and all His saints are the hope andthe ultimate goal of the entire pilgrimage of human life.